空间RCCR机构的力分析与仿真 - 庄森; 虞启辉; 刘晨曦; 牛清河 (Jixie chuandong)
Force analysis about space RCCR mechanism is carried out by show force pair method.At the same time,this mechanism is simulated by computer-aided dynamic analysis software COSMOSMotion.Finally,the simulation results and theoretical analysis results are consistent by typical movement constraint force.A number of important conclusions is obtained.